CD5 acts as a tyrosine kinase substrate within a receptor complex comprising T-cell receptor zeta chain/CD3 and protein-tyrosine kinases p56lck and p59fyn. - Burgess, K E (1992)
T-cell antigens including CD2, CD4, CD6, CD8, and CD28 serve as coreceptors with the T-cell receptor (TCR)/CD3 complex in control of T-cell growth. The molecular basis by which these antigens fulfill this role has remained a major issue. An initial clue to this question came with our finding that the sensitivity of in vitro kinase labeling (specifically using protein-tyrosine kinase p56lck) allowed detection of a physical association between CD4-p56lck and the TCR/CD3 complexes. Another T-cell antigen, CD5, is structurally related to the macrophage scavenger receptor family and, as such, can directly stimulate and/or potentiate T-cell proliferation. In this study, we reveal that in Brij 96-based cell lysates, anti-CD5 antibodies coprecipitated TCR zeta chain (TCR zeta)/CD3 subunits as well as the protein-tyrosine kinases p56lck and p59fyn. Conversely, anti-CD3 antibody coprecipitated CD5, p56lck, and p59fyn. Indeed, anti-CD5 and anti-CD3 gel patterns were virtually identical, except for a difference in relative intensity of polypeptides. Anti-CD4 coprecipitated p56lck, p32, and CD3/TCR zeta subunits but precipitated less CD5, suggesting the existence of CD4-TCR zeta/CD3 complexes distinct from the CD5-TCR zeta/CD3 complexes. Consistent with the formation of a multimeric CD5-TCR zeta/CD3 complex, anti-CD5 crosslinking induced tyrosine phosphorylation of numerous T-cell substrates, similar to those phosphorylated by TCR zeta/CD3 ligation. Significantly, as for TCR zeta, CD5 was found to act as a tyrosine kinase substrate induced by TCR/CD3 ligation. The kinetics of phosphorylation of CD5 (t1/2 = 20 sec) was among the earliest of activation events, more rapid than seen for TCR zeta (t1/2 = 1 min). CD5 represents a likely TCR/CD3-associated substrate for protein-tyrosine kinases (p56lck or p59fyn) and an alternative signaling pathway within a multimeric TCR complex.